Burden of Care Among Caregivers of Mentally Ill Patient at Tertiary Level Hospital - Regmi, Kalpana; Bista, Rebika (Journal of College of Medical Sciences-Nepal, 2024)
Abstract Introduction Caregivers of people with mental illnesses are a key support system. The caregivers suffer significant burden as a result of the care giving role. The level of burden of caregivers among people with mental illness is considered to be a negative impact on the care provided by the family to their patient. Methods A descriptive cross sectional research design was used. A total of 96 care givers were selected using purposive sampling technique. The purpose of the study was to assess the burden of care of mentally ill patient among care givers in a selected hospital. The Zarit Burden Interview Scale was use to assess burden care. All the collected data were analyzed by using descriptive statistical method such as frequency, mean, percentage, standard deviation and chi square test to find out the association with level of burden of care and selected demographic variables. Results Nearly one third (31.3%) of caregivers had moderate level of burden and 9.4% of them had severe burden of care. There was significant association between the level of burden of care with sex of the caregivers and their educational level. Conclusion Caregivers had moderate level of burden of care while caring their mentally ill patient. In order to reduce their burden of care, self-help and psycho-educational programs will be effective. This action addresses to improve their perceived knowledge on mental illness and develop coping skills to deal with their patient’s behavior. Key Words: Burden; Caregivers; Mentally ill patient.